Tribology - Fundamentals and Advancements 2013
DOI: 10.5772/55470
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of the Ratio of the Hardness to the Reduced Elastic Modulus for Abrasion

Abstract: Additional information is available at the end of the chapter http://dx.doi.org/10.5772/55470 . IntroductionModelinμ tνe wear rate is a complex process. Tνe several possibilities of cνemical, pνysical and mecνanical cνanμes at tνe interface are tνe most probable reasons for tνis [ ]. In tνis manner, it is reasonable to consider tνe wear rate as a stocνastic process [ , ], and indeed tνis approacν was taken into account by Arcνard [ ], wνen νe formulated νis well-known model. Since tνen, tνe majority of availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…The TM-1 coatings exhibited the highest H 3 /E 2 ratio, meaning the best elastic properties, followed by TM-0 and TM-2. The H 2 /2E ratio describes resistance to the effect of external forces, known as the modulus of resilience [40]. It can be seen that the TM-0 has the highest H 2 /2E ratio, indicating a good ability to recover after applying external forces.…”
Section: Mechanical Propertiesmentioning
confidence: 89%
See 2 more Smart Citations
“…The TM-1 coatings exhibited the highest H 3 /E 2 ratio, meaning the best elastic properties, followed by TM-0 and TM-2. The H 2 /2E ratio describes resistance to the effect of external forces, known as the modulus of resilience [40]. It can be seen that the TM-0 has the highest H 2 /2E ratio, indicating a good ability to recover after applying external forces.…”
Section: Mechanical Propertiesmentioning
confidence: 89%
“…It can be observed that both the H and E of the coated samples decrease with Mg addition in the Ti-doped HAP structure. The H/E ratio is called "plasticity index" and defines the elastic strain of a material to its failure [40]. A high value of this ratio indicates good elastic properties and good adhesion of the coating to the substrate.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in Pintaude (2013), the lower value of the E/H results in a low cutting efficiency. Hence, this parameter was utilized to choose the mechanical properties, in particular the elastic modulus and the hardness of the phases to be scratched.…”
Section: Soft Materials -Nanoindentationmentioning
confidence: 92%
“…H³/E² data were obtained in ball-on-disc systems, and were proportional to the transition load from the elastic contact to plastic contact (PINTAUDE, 2013). The hardness and elastic modulus were not separately determined.…”
Section: Mechanical Properties Effects On the Abrasionmentioning
confidence: 99%